Influence of substrate on structural and transport properties of LaNiO3 thin films prepared by pulsed laser deposition - Cichetto, L. [UNESP]; Sergeenkov, S.; Diaz, J. C.C.A.; Longo, E. [UNESP]; Araújo-Moreira, F. M. (AIP Publishing, 2017)
We report the structural and transport properties of LaNiO3 thin films prepared by pulsed laser deposition technique. To understand the effects of film thickness, lattice mismatch and grain size on transport properties, various oriented substrates were used for deposition, including single-crystalline SrLaAlO4 (001), SrTiO3 (100) and LaAlO3 (100). To achieve a high quality LaNiO3 thin films, the vital parameters (such as laser fluence, substrate temperature, oxygen pressure, and deposition time) were optimized. The best quality films are found to be well textured samples with good crystalline properties.